Analysis of Student Attitudes towards E-Learning: Case of Computer Science Students’ in Nigeria - Ogunnowo, Olumayowa Oluwafemi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The approach of students‟ to new innovations (technologies) signifies the basic aspect that will accustom their stance in respect to e-learning & alertness in utilizing them. Usage of personal computer, network and portable devices (mobile) has captivated the enthusiasm between different students that benefit from it as an educational tool. According to (UNESCO, 2006); the rise in numerous developing countries concerning e-learning where it can conceivably take care of a rising demand for learning and tackle the deterioration of experienced instructors. Moreover, it has been discovered that students‟ attitude and belief towards e-learning is viewed as achievement determinant of imminent e-learning activities. As reported by (El-Gamal & El-Aziz, 2011); by College students in developing countries have differing perspective in connection to e-learning, yet generally their dispositions are sure. Therefore, the research will explicitly analyze the overall attitude of students towards e-learning in Nigeria, in which as a researcher I have highlighted above. In this research, mixed approach is going to be used and as a methodology the researcher will collect and examine data through qualitative and quantitative method; then utilize Statistical Package for the Social Science (SPSS). Moreover, semi-structured interviews with the students on voluntary basis will be used. Conclusion and suggestions will be presented at the end of the research as a contribution to this field. Keywords: e-learning, innovations, computer science students, student attitude.

ÖZ: Öğrencilerin gelişen teknolojiye karşı olan tutumları, onların uzaktan öğretime karşı olan farkınfdalıklarının göstergesidir. Bilgisayar, laptop ve taşınabilir diğer cihazlarında öğrencilerin hayatında eğitsel bir araç olarak büyük bir etkisi olmuştur. (UNESCO, 2006) da yapmış olduğu bir araştırmada bu oranın gittikçe arttığı görülmüştür. Bu bağlamda, bu araştırmanın amacı Nijeryada ki öğrencvilerin uzaktan eğitime karşı olan tutumlarını genel bir çerçevede incelemektir. Araştırmada hem nitel hem de nicel metodoloji kullanılarak data toplanılmıştır. Nicel kısım için bir uzman eşliğinde veriler analiz edilirken, nitel de ise araştırmacı içerik analizi kullanarak data analiz edilmiştir. Sonuç ve tartışma kısmında bulgular verilmiştir. Bunun yanında gelecekde ki çalışmalara ne gibi katkılarda bulunabilir şeklinde araştırmacı tarafından önerilerde bulunulmuştur. Anahtar kelimeler: elektronik ogrenme, buluslar, ogrencilerin tutumlari, beceriler.
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technologies, 2016. Supervisor: Assist. Prof. Dr. Bengi Sonyel.
Keywords: Computer Education and Instructional Technologies; Information and Communication Technologies in Education Nigeria; Education - Computer network resources; Educational Technology - E-Learning; Teaching - Computer network resources; e-learning; innovations; computer science students; student attitude